Kesetaraan Pasien Peserta BPJS dan Non-BPJS dalam Memperoleh Pelayanan Kesehatan di Rumah Sakit - Andryawan; Aryanti Agripina Winata; Kearen Elvira Naftali; Marcia Gladys Rumambi; Allaysha Adindaputri Kirani (Jurnal Hukum Caraka Justitia, 2026)
Since 2014, the government has been implementing the JKN BPJS program to meet the basic health needs of the poor. However, there are still disparities in service between BPJS and non-BPJS patients, such as complicated processes, limited facilities, restrictions on hospitalization, and discriminatory treatment by medical personnel. The main focus of this study is on the supervision carried out by the government to ensure equality in medical services. This study is a normative legal analysis based on secondary data obtained from literature reviews, employing a statutory and conceptual approach. The results of the study show that although the government has carried out its supervisory duties, the implementation is still not optimal, and the suboptimal supervision by relevant institutions (BPJS Supervisory Board, DJSN, and BPRS) has caused inequality in medical services. Even new policies such as the Standard Inpatient Class (KRIS), which aims to eliminate disparities, have not been optimally implemented. Based on the study's results, it was concluded that fairness in services is necessary to ensure equal treatment and access for all patients, without discrimination. Therefore, it is recommended that the government and supervisory agencies consistently enhance the effectiveness of supervision and provide training and guidance to medical personnel to ensure fair services are provided without discrimination based on insurance status.